2007
DOI: 10.1111/j.1474-9726.2007.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction extends the chronological lifespan of Saccharomyces cerevisiae independently of the Sirtuins

Abstract: SummaryCalorie restriction (CR) extends the mean and maximum lifespan of a wide variety of organisms ranging from yeast to mammals, although the molecular mechanisms of action remain unclear. For the budding yeast Saccharomyces cerevisiae reducing glucose in the growth medium extends both the replicative and chronological lifespans (CLS). The conserved NAD + -dependent histone deacetylase, Sir2p, promotes replicative longevity in S. cerevisiae by suppressing recombination within the ribosomal DNA locus and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
179
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(200 citation statements)
references
References 64 publications
17
179
0
2
Order By: Relevance
“…7B). Similarly, Sir2p is not required for calorie restriction-mediated chronological life span extension in yeast (66,67). Instead, our results are consistent with other studies that found that blocking sphingolipid synthesis leads to chronological life span extension.…”
Section: Growth In the Absence Of Inositol Leads To Chronological Lifsupporting
confidence: 83%
See 1 more Smart Citation
“…7B). Similarly, Sir2p is not required for calorie restriction-mediated chronological life span extension in yeast (66,67). Instead, our results are consistent with other studies that found that blocking sphingolipid synthesis leads to chronological life span extension.…”
Section: Growth In the Absence Of Inositol Leads To Chronological Lifsupporting
confidence: 83%
“…In yeast, many of these stresses are associated with chronological life span extension (63,66). Consistent with the view that inositol deprivation is a stress provoking growth condition in yeast, we found that wild type cells growing in medium lacking inositol exhibit increased chronological life span (Fig.…”
Section: Growth In the Absence Of Inositol Leads To Chronological Lifsupporting
confidence: 73%
“…Respiration induced by caloric restriction or by a non-fermentable carbon source seems to induce good mitochondrial metabolic activity with low ROS leakage from the respiratory chain. Many authors reported that a restricted dietary intake increased the rate of oxygen consumption, thus indicating an increase in mitochondrial respiration [43,44]. Furthermore, an evaluation of the GSH and GSSG levels also suggests that better mitochondrial activity might promote longevity by triggering mechanisms that protect cells against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Our previous findings suggest that prolonged stationary phase survival of chronologically aging yeast in low glucose results, at least in part, from decreased production of acetic acid. 11 In addition to dietary restriction, inhibition of the target of rapamycin (TOR) kinase and/or deletion of the gene coding for the ribosomal S6 kinase homolog, SCH9, are both known to increase replicative life span and CLS in yeast, [25][26][27][28] as well as the lifespan of C. elegans 29,30 and D. melanogaster.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%